2004
DOI: 10.1063/1.1687531
|View full text |Cite
|
Sign up to set email alerts
|

Investigating magnetization dynamics in permalloy microstructures using time-resolved x-ray photoemission electron microscope

Abstract: We present results of a direct imaging approach to visualize the dynamics of magnetic domains on the nanosecond scale. The experiments are carried out by means of an x-ray photoemission electron microscope (X-PEEM) in a stroboscopic mode and exploit the intrinsic time structure of the synchrotron radiation delivered by the storage ring facility ESRF (Grenoble). In this way we combine the high lateral resolution of a PEEM with a subnanosecond time resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In the experiments reported here the pulsed magnetic field is stronger, which results in the formation of additional domains to reduce the stray field energy. Recently, Kuksov et al 25 reported on the dynamics in permalloy elements of comparable size. The amplitude of the pulsed magnetic field is comparable to our experiments, but the pulse lasts over several nanoseconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experiments reported here the pulsed magnetic field is stronger, which results in the formation of additional domains to reduce the stray field energy. Recently, Kuksov et al 25 reported on the dynamics in permalloy elements of comparable size. The amplitude of the pulsed magnetic field is comparable to our experiments, but the pulse lasts over several nanoseconds.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Other experiments using scanning Kerr microscopy focus onto the eigenmodes of the magnetization in magnetic elements 18 and the gyrotropic motion of a central vortex in magnetic thin film elements. 19 In addition to the magneto-optical methods other time-resolved imaging techniques, namely, time-resolved x-ray photoemission electron microscopy ͑XPEEM͒ and magnetic transmission x-ray microscopy ͑MTXM͒ demonstrated great potential [20][21][22][23][24][25] and were used for similar studies. An overview over different methods for magnetic imaging can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Photoelectron emission microscopy ͑PEEM͒ has been used for many years for imaging magnetization structures 2 and is one of the most promising methods for imaging magnetic domains both at high lateral resolution and on a short time scale due to the parallel imaging technique. 3,4 The most widely employed technique for obtaining magnetic contrast is the x-ray magnetic circular dichroism ͑XMCD͒ in absorption. [5][6][7] Electrons are excited from core levels into the unoccupied spin-split valence states by circularly polarized x-ray photons.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the element-specific electronic structure of matter can be dynamically observed by SR-based time-resolved spectro-microscopy. In particular, spectro-microscopy combined with the X-ray magnetic circular dichroism effect has been performed at several SR facilities in the world, [99][100][101][102][103][104] and is a suitable technique for observing the domain motion of micro-magnetic structures in the sub-nanosecond range. Ultrafast magnetization dynamics in micron-sized magnetic materials is now one of the important issues relates to the development of fast and high-density data storage devices.…”
Section: Pump-probe Time-resolved Measurementsmentioning
confidence: 99%